Muslim Youth Under Sharia Regime in Aceh: From Accommodation to Resistance - Khamami Zada; Windy Triana; Nur Hidayah; Ummi Kultsum; Fathudin (Al-Ihkam, Jurnal Hukum dan Pranata Sosial, 2022)
In the context of shari’a implementation in Aceh, there has been resistance among young people wanting freedom and openness in public space with its modernity values. This study aims at investigating the responses of Aceh’s young people to the implementation of Sharia in Aceh and how it implies for the Sharia law enforcement in the region. This is a socio-legal research relying on interviews and focused-group discussions as data collection methods. Respondents consist of young people aged 20-25. This research finds out that there has been a normalization of sharia in the Acehnese society with young people tending to accept sharia in Islamic tenets, propagation, attires, economic system, and penal system. Those who were born after or a while before sharia was implemented for the first time tend to get used to the sharia and consider it a part of their normal life. Their responses vary, from accommodation, adaptation, compromise to resistance. The resistance leads to the agency and creating a counterspace as their comfort zone to express creativity. In turn, this religiosity model contributes to sharia's moderatization in Aceh. Therefore, there is a need for the Aceh local government to maintain and develop spaces for young people to express creativity while maintaining sharia as a part of their lives.